The Effect of Resin Matrix on the Properties of CF/PEI and CF/PAEK Thermoplastic Composites - Wencai Wang; Jindong Zhang; Dongting Gao; Kun Yu; Gang Liu; Ming Wang; Jianan Yao (International Journal of Polymer Science, 2023)
As the adhesive for composites, the resin matrix directly impacts the molding process and product performance of thermoplastic composites (TPCs). Carbon fiber-reinforced polyetherimide (CF/PEI) and polyaryletherketone (CF/PAEK) composites were prepared by a compression molding process. The interface, interlaminar, and low-speed impact properties of TPCs were studied. The results show that the interfacial shear strength of the CF/PEI composite is ~116 MPa, while the CF/PAEK composite is ~78 MPa. However, the interlaminar and low-speed impact performance of CF/PAEK is better than CF/PEI. Type I fracture toughness (GIC) and type II fracture toughness (GIIC) of CF/PEI are ~1051 MPa and ~1060 MPa. But those of CF/PAEK are ~1786 MPa and ~2584 MPa, respectively. The compressive strength after the impact of CF/PAEK (~321 MPa) is 40% higher than CF/PEI (~230 MPa).